Revisiting dependency and development in Latin America - Domingues, José Maurício (Ciência & Trópico, 2013)
ABSTRACT This article revisits the main thesis of Cardoso and Faletto’s classic Development and Dependency in Latin America, confronting the re-evaluation Cardoso himself has recently made of the book. It revises and updates some of its theses, relating them to global changes, in variation also with Cardoso’s newly found perspective. Development is thereby revisited in the third, contemporary phase of global modernity. The article closes with a brief discussion of critical theory. KEYWORDS: Cardoso. Development. Global changes. Latin America. Revisitando dependência e desenvol-vimento na América Latina RESUMO Este artigo revisita a principal tese de Cardoso e Faletto sobre o desenvolvimento e dependência clássicos na América Latina, enfrentando a reavaliação recentemente feita, de Cardoso, do livro. Ele revisa e atualiza algumas das suas teses, relacionando-as às mudanças globais, em variação também com a perspectiva recém encontrada pelo autor. O desenvolvimento revisita na terceira fase contemporânea da modernidade global. O artigo termina com uma breve discussão da teoria crítica. PALAVRAS-CHAVE: Cardoso. Desenvolvimento. Mudanças globais. América Latina.